Advocacy and Rationing Are Compatible - Claude Gratton and Margaret Keatings (HealthcarePapers, 2001)
In his paper, Peter Ubel attempts to make the case for "bedside rationing" by clinicians in order to help control healthcare costs. This commentary addresses a number of conceptual, logical and linguistic problems with Dr. Ubel's paper, challenges his apparently "heretical" view of advocacy, but provides additional support for his central claim that physicians should do bedside rationing.